Do Green Innovation, Carbon Emission Disks Affect Company Value with Environmental Performance as A Moderator? - Septiani , Rahmalita; Hernawati, Erna (KnE Social Sciences, 2024)
This research is a quantitative study that aims to determine the effect of green innovation as measured by four indicators of disclosure items and carbon emission disclosure on company value, moderated by environmental performance. The sample of this research was taken from manufacturing sector companies listed on the Indonesia Stock Exchange in the 2020-2022 period, which were selected based on the purposive sampling method. Data were obtained from 37 companies, with a total sample size of 111. The results of the test indicate that (1) Green innovation does not have a significant influence on company value. (2) Carbon emission disclosure does not have a significant influence on company value. (3) Environmental performance does not strengthen the relationship between green innovation and company value, and (4) Environmental performance does not strengthen the relationship between carbon emission disclosure and company value. According to the results, it can be observed that these variables are less effective in influencing company value, suggesting the need for further research. Keywords: company value, green innovation, carbon emission disclosure, environmental performance